Elucidating the role of dust concentrations and initial turbulence on rice flour explosion - Wan Zaiton, Wan Sulaiman; Mohd Fadzil, Mohd Idris; Jolius, Gimbun (Elsevier Ltd, 2025)
The explosibility and severity characteristics of rice flour at different concentrations and ignition delay times were investigated experimentally. Meanwhile, the turbulent flow and dust dispersion that affect the dust explosion in a Siwek 20 L spherical chamber were elucidated using computational fluid dynamics (CFD) simulation. The dust injected at 21 bar from the bottom of the chamber was observed to move in an upward direction until it hit the wall and recirculated, then dispersed all over the chamber. The turbulent kinetic energy and velocity magnitude in the camber were observed to increase significantly in the first 20 ms, then reduce thereafter. It was found that the rice flour explosibility is much higher at a higher ignition delay time (tv) of >60 ms, while the lowest explosibility was observed at 20 ms due to the low concentration of dust at the point of ignition. Contrary to the explosibility, the maximum explosion overpressure (Pmax) of dried rice flour is the highest at the tv of 20 ms compared to those obtained at 60 and 100 ms, owing to the densely packed dust at the centre of the chamber. This study may provide a useful insight into the dust explosibility of rice flour dust cloud.